Issue Information TOC. Issue 1 (19th December 2019) - Unknown
Abstract : Cover : In Klimas et al. (https://doi.org/10.1002/cpcy.67 ), Representative results from sagittal sections of mouse striatum. Pre‐expanded samples were stained with DAPI (blue) and labeled for tyrosine hydroxylase (green), synaptophysin (red), and α‐internexin (magenta). Pre‐expansion samples are shown on the left; post‐expansion on the right. (A, B ) Successful completion resulted in a 5.27‐fold expansion of the tissue from A to B. (C, D ) Magnified images of outlined regions in A and B, respectively. (E, F ) A separate sample that was over‐homogenized shows distortion and loss of fluorescent signals for tyrosine hydroxylase and synaptophysin. All images were taken on a spinning‐disk confocal microscope using a 1.1‐NA 40× (A‐D ) or 0.95‐NA 20× (E, F ) water‐immersion objective. Scale bars: 10 µm (A, B ; post‐expansion physical size 52.7 µm); 5 µm (C, D ; post‐expansion physical size 26.4 µm); (E, F ) 100 µm.